2021
DOI: 10.1590/pboci.2021.093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Social Variables Association on the Frequency of Intellectual Disability Persons to Dental Care

Abstract: Objective: To evaluate the association of oral health indicators and social variables on the frequency of visit to the dentist by persons with intellectual disability (ID). Material and Methods: The study comprised a sample consisting of 149 participants with ID, aged from 11 to 29 years, from non-governmental institutions. Semi-structured interviews were held to collect sociodemographic and psychosocial information with their parents/guardians, followed by oral health evaluations in accordance with World Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In addition to discrimination, stigma, and inequality, PwD face a range of general and systemic health conditions, such as poor oral health, compared to people without disabilities, resulting in reduced access to basic healthcare services. 1,[3][4][5] The dentists' inability to provide adequate dental care for PwD stems from a lack of specialized clinical experience and theoretical knowledge regarding their specific oral care needs. 3 There is an evident shortage of educational opportunities to equip dental students with sufficient expertise in providing dental services to PwD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to discrimination, stigma, and inequality, PwD face a range of general and systemic health conditions, such as poor oral health, compared to people without disabilities, resulting in reduced access to basic healthcare services. 1,[3][4][5] The dentists' inability to provide adequate dental care for PwD stems from a lack of specialized clinical experience and theoretical knowledge regarding their specific oral care needs. 3 There is an evident shortage of educational opportunities to equip dental students with sufficient expertise in providing dental services to PwD.…”
Section: Introductionmentioning
confidence: 99%
“…Health status is determined by several factors, including socioeconomic, cultural, and environmental factors and access to healthcare services. In addition to discrimination, stigma, and inequality, PwD face a range of general and systemic health conditions, such as poor oral health, compared to people without disabilities, resulting in reduced access to basic healthcare services 1,3–5 …”
Section: Introductionmentioning
confidence: 99%
“…The higher incidence of oral diseases in this population can also be associated with certain social factors, including the difficulties encountered in accessing dental care, such as the inadequate structure and organization of these oral health services as well as the lack of trained professionals and limited treatment options. In addition to having reduced access to oral health services, individuals with disabilities often experience lower resolution of their dental treatments and health care demands 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to having reduced access to oral health services, individuals with disabilities often experience lower resolution of their dental treatments and health care demands. [8][9][10][11] According to Albrecht et al, 12 the crisis in health accessibility for PwDs can promote a gradual decrease in the quality of oral health care in this population. Therefore, public health and educational policies regarding the provision of adequate services and oral health care for PwDs are important because it has been observed that possible sequelae associated with oral diseases and low levels of hygiene need greater attention among professionals and caregivers of PwDs.…”
Section: Introductionmentioning
confidence: 99%